Mathematics for matriculation - Abdul Hadi Yaakub; Ong, Beng Sim; Tan, Chong Eng; Lye, Min Soon; Lee, Khaik Yong; Che Noorlia Noor; Maheran Nuruddin; Miskiah Dzakaria (Oxford Fajar Sdn Bhd, 2019)
This books is a comprehensive coursebook written for students studying Mathematics in local matriculation courses.This coursebook aims to stimulate students' interest in mathematics and help them gain a firm understandung of important principles and concept in mathematics.